An Unprecedented Arctic Ozone Depletion Event During Spring 2020 and Its Impacts Across Europe. Issue 3 (30th January 2023) - Petkov, Boyan H.; Vitale, Vito; Di Carlo, Piero; Drofa, Oxana; Mastrangelo, Daniele; Smedley, Andrew R. D.; Diémoz, Henri; Siani, Anna Maria; Fountoulakis, Ilias; Webb, Ann R.; Bais, Alkiviadis; Kift, Richard; et al.
Abstract: The response of the ozone column across Europe to the extreme 2020 Arctic ozone depletion was examined by analyzing ground‐based observations at 38 European stations. The ozone decrease at the northernmost site, Ny‐Ålesund (79°N) was about 43% with respect to a climatology of more than 30 years. The magnitude of the decrease declined by about 0.7% deg −1 moving south to reach nearly 15% at 40°N. In addition, it was found that the variations of the ozone column at each of the selected stations in March‐May were similar to those observed at Ny‐Ålesund but with a delay increasing to about 20 days at mid‐latitudes with a gradient of approximately 0.5 days deg −1 . The distributions of reconstructed ozone column anomalies over a sector covering a large European area show decreasing ozone that started from the north at the beginning of April 2020 and spread south. Such behavior was shown to be similar to that observed after the Arctic ozone depletion in 2011. Stratospheric dynamical patterns in March–May 2011 and during 2020 suggested that the migration of ozone‐poor air masses from polar areas to the south after the vortex breakup caused the observed ozone responses. A brief survey of the ozone mass mixing ratios at three stratospheric levels showed the exceptional strength of the 2020 episode. Despite the stronger and longer‐lasting Arctic ozone loss in 2020, the analysis in this work indicates a similar ozone response at latitudes below 50°N to both 2011 and 2020 phenomena. Plain Language Summary: The winter polar vortex isolates a huge volume of air from external impacts that, in the absence of the sunlight, leads to a great deal of cooling and the formation of polar stratospheric clouds. Chemical reactions taking place in these clouds contribute to ozone destruction. Such spring‐time ozone depletions are regularly observed in Antarctica, but usually do not occur in the Arctic where the vortex is much less intense. However, in the past three decades several similar episodes occurred in the Arctic and the most marked of them took place in the 2011 and 2020 springs. The response of the ozone layer over Europe to the 2020 episode was studied here by analyzing the data from 38 ground measurement stations. It was found that there was a nearly 43% decrease in ozone in the Arctic, and, as it spread southward, a reduction of 15% in mid‐latitudes 15–20 days later. This spread was attributed to the transport of ozone‐poor air from the Arctic to the south after the vortex breakup. Despite the stronger depletion in 2020 and some differences in the movement of air, the response of the ozone layer was quite similar in the springs of both 2011 and 2020. Key Points: The 2020 ozone depletion in the Arctic was found to impact the ozone in the mid‐latitude European areas The magnitude of ozone decrease in the southern regions declined with respect to that in the Arctic and occurred with a delay up to 20 days Such a response was similar to that observed in 2011 and both were considered a result of ozone‐poor air masses transported southward